Solar Light Photodetectors Based on Nanocrystalline Zinc Oxide Cadmium Doped/p-Si Heterojunctions - Ameen, Bestoon Anwer Hamad; Yildiz, Abdulkadir; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Springer, 2019)
The transparent undoped and Cd doped ZnO thin films were deposited on p-type Si substrates to fabricate Cd-ZnO/p-Si diodes. The Cd doped ZnO thin films exhibited a polycrystalline structure. The transmittance measurements indicate that the films have transparency ranging from 47% to 92% for the UV and visible regions. The optical band gap of the films were found to be ranging from 3.27 to 3.19 eV with Cd content. The photoelectrical properties of the diodes under various illuminations were analyzed. The undoped and Cd doped ZnO thin films/p-silicon devices exhibit a photovoltaic behavior with the obtained photovoltaic parameters. The continuous distribution of interface states in the diodes is analyzed by capacitance voltage (C-V) measurements. The diode having 0.1% Cd doped Zno showed the highest photosensitivity in all the diodes with the photoresponsivity of 3.6 x10(-4). We suggest that the fabricated CdZnO based diodes can be used as photodetector in optic and optoelectronic communications.
Keywords: Zinc oxide; Cadmium doped photodiode; Photoresponse properties; Sol-gel; Optical properties